Hydrologic and hydrodynamic modelling of extreme flood events to assess the impact of climate change in a large basin with limited data. (21st August 2015) - Amir, M.S.I.I.; Khan, M.M.K.; Rasul, M.G.; Sharma, R.H.; Akram, F.
Abstract: Flood modelling of a large basin like the Fitzroy is a difficult task due to its large catchment size, the long duration of flood events, the non‐uniform spatial distribution of rainfall and a lack of required data for modelling purposes. This paper presents a systematic methodology for the flood modelling of the Fitzroy Basin using hydrologic and hydrodynamic modelling approach with Geographic Information System (GIS) capabilities. This study developed five flood scenarios analysing historical flood events and considering three impacts of climate change: upstream subcatchments flooding, local rainfall fluctuations and sea level rise. A hydrologic model was developed within the wider Fitzroy Basin with the five upstream subcatchments and the upper Fitzroy subcatchment in order to simulate discharge data for these scenarios at the Gap measurement location. An integrated hydrologic–hydrodynamic model was developed for the lower Fitzroy subcatchment where output discharges of the hydrologic model were considered as the upstream boundaries. The peak flood levels, peak flow rates and flood inundation durations at Rockhampton city were identified using this integrated model. GIS capabilities were specially used for automatic watershed delineation and river cross‐section extraction from Digital Elevation Model (DEM) data. The methodology proposed here is a case study and can be applied to other similar basins or catchments.